The influence of clinic care on perceptions and knowledge of non-communicable diseases and physical activity from a low-resourced community: a mixed-method study - S. J. Makamu-Beteck; S. J. Moss; M. Cameron; F. G. Watson (BMC, 2022)
Abstract Background Health promotion for the management of risk factors for non-communicable diseases (NCDs) is an integral part of standard care in South Africa. Most persons presenting with NCDs utilise public primary health care centres for disease management. This mixed-methods study aimed at expanding current understanding of the the influence of standard clinic care (usual care) on perceptions and knowledge of risk factors for NCDs and physical activity (PA) among persons from a low-resourced community. Qualitatively the perceptions of women from a low-resourced community about risk factors for NCDs and PA were explored throughout 24-weeks of standard clinic care. Parallel quantitative data was collected to describe changes in risk factors for NCDs and trends in self-reported knowledge about risk factors of NCDs and PA. Method A convergent-parallel mixed-methods research design was used. The study was carried out in a public primary health care setting, in the North West Province, South Africa. From a convenience sample of 100 participants, 77 African women aged between 34 and 79 years were recruited for the study. Data were collected at three time-points including baseline, 12 weeks, and 24 weeks of a standard clinic care health-promotion programme. The qualitative data was collected during focus group discussions, and the quantitative data included questionnaires on knowledge of physical activity and risk factors for NCDs as well as anthropometric and biological measurements. Qualitative and quantitative data were analysed independently for each phase and then consolidated for interpretation. All data was collected in the same setting. Results Participants' initial understanding and perceptions of NCD risk factors were poor. Qualitative findings showed that participants knew little about the specific physical activity they could engage in and the role of PA in NCD management. Participants preferred low-intensity activities. Heart-disease knowledge improved significantly at 12 weeks intervention compared to baseline MD = -3.655, p < 0.001. There were improvements in PA knowledge at 12 weeks from baseline MD = -0.625 p = 0.02. There were significant weight (MD = 1.420, p = 0.002) and waist circumference reductions (MD = 0.621, p = 0.02) from baseline to 24 weeks. Conclusion Standard clinic care improved knowledge of physical activity and risk factors for NCDs, but perceptions of risk factors for NCDs and PA were unchanged. This study offers insight into the perceptions held by women from a low-resource setting and how future interventions to manage and prevent NCDs should be structured. Trial registration PACTR201609001771813 .